BET Inhibitor JQ1 Blocks Inflammation and Bone Destruction. (July 2014) - Meng, S.; Zhang, L.; Tang, Y.; Tu, Q.; Zheng, L.; Yu, L.; Murray, D.; Cheng, J.; Kim, S.H.; Zhou, X.; Chen, J.
BET proteins are a group of epigenetic regulators controlling transcription through reading acetylated histone tails and recruiting transcription complexes. They are considered as potential therapeutic targets in many distinct diseases. A novel synthetic bromodomain and extraterminal domain (BET) inhibitor, JQ1, was proved to suppress oncogene transcription and inflammatory responses. The present study was aimed to investigate the effects of JQ1 on inflammatory response and bone destruction in experimental periodontitis. We found that JQ1 significantly suppressed lipopolysaccharide (LPS)-stimulated inflammatory cytokine transcription, including interleukin (IL)-1β, IL-6, and tumor necrosis factor alpha (TNF-α), as well as receptor activator of nuclear factor kappa-B ligand (RANKL)-induced osteoclast markers, such as c-Fos, nuclear factor of activated T-cells, cytoplasmic, calcineurin-dependent 1 (NFATc1), tartrate-resistant acid phosphatase (TRAP) and cathepsin K in vitro . JQ1 also inhibited toll-like receptors 2/4 (TLR2/4) expression and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) phosphorylation and nuclear translocation. Chromatin immunoprecipitation and quantitative polymerase chain reaction (ChIP-qPCR) revealed that JQ1 neutralized BRD4 enrichment at several gene promoter regions, including NF-κB, TNF-α, c-Fos, and NFATc1. In a murine periodontitis model, systemic administration of JQ1 significantly inhibited inflammatory cytokine expression in diseased gingival tissues. Alveolar bone loss was alleviated in JQ1-treated mice because of reduced osteoclasts in periodontal tissues. These unprecedented results suggest the BET inhibitor JQ1 as a prospective new approach for treating periodontitis.